ROTATING-DISK ELECTRODES - THE THEORY OF CHRONOAMPEROMETRY AND ITS USE IN MECHANISTIC INVESTIGATIONS - Compton, R; Laing, M; Mason, D; Northing, R; Unwin, P (1988)
A general computational strategy is presented for the calculation of the chronoamperometric responses arising from potential-step experiments at rotating disc electrodes. The method is applicable to a wide range of electrode reaction mechanisms and theoretical results are given for single- and double-potential-step experiments for ECE, DISP1, DISP2, EC' and CE reactions. For the last, the treatment is extended to cover the case where reactants have grossly unequal diffusion coefficients. Steady-state behaviour is also deduced. The extent to which the various mechanistic pathways can be distinguished is identified and the necessary experiments defined.